2022
DOI: 10.3389/fenvs.2022.1033909
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oil characteristics on the performance of shoreline response operations: A review

Abstract: Marine oil spills are serious ecological disasters that have massive adverse impacts on the environment. The impacts are even worse once the spilled oil is stranded on a shoreline. A series of shoreline cleanup methods are deployed to remove spilled oil, but their performance can be affected by the stranded oil. This review therefore comprehensively investigates the characteristics of spilled oil on the shoreline and explores their effects on the effectiveness of shoreline response operations. First, the five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 96 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…With regard to coastlines, the behavior of spilled hydrocarbons can be affected by several factors. As Chen et al [47] showed, the type and composition of the spilled oil are the main factors that influence oil adhesion, as they are closely related to its physical properties, including its viscosity and density. Authors of [48] also pointed out that heavier oils are more adherent to the coastal surface than light oils, and that less fresh oils are also more adherent.…”
Section: Introduction-coastal and Ocean Concernsmentioning
confidence: 99%
“…With regard to coastlines, the behavior of spilled hydrocarbons can be affected by several factors. As Chen et al [47] showed, the type and composition of the spilled oil are the main factors that influence oil adhesion, as they are closely related to its physical properties, including its viscosity and density. Authors of [48] also pointed out that heavier oils are more adherent to the coastal surface than light oils, and that less fresh oils are also more adherent.…”
Section: Introduction-coastal and Ocean Concernsmentioning
confidence: 99%
“…The sources of wastewater are rainwater and meltwater, which are contaminated with oil, oil products, reagents, and mechanical impurities, flowing through the sites of technological installations and tank farms. Accidental oil spills pose a special danger of environmental pollution, which leads to the pollution of a water area of 12 km 2 per 1 ton of oil [Xinya et al, 2022;Fingas, 2017].…”
Section: Introductionmentioning
confidence: 99%